INTERNALISASI MODEL PEMBELAJARAN TGT BERBASIS PERMAINAN TRADISIONAL TERHADAP KETERAMPILAN NUMERASI DAN KETERAMPILAN SOSIAL PESERTA DIDIK - Hartinawanti, Hartinawanti; Nurddin, Dina Firliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to: 1) describe the internalization of the TGT learning model based on traditional games among fourth-grade students at SD Negeri 1 Labalawa; 2) analyze the significant relationship between the traditional game-based TGT learning model and students' numeracy skills; 3) analyze the significant relationship between the traditional game-based TGT learning model and students' social skills. This research uses a quantitative method with a correlational design. The sampling technique uses purposive sampling, resulting in a research sample of 31 students from the fourth grade of State Elementary School 1 Labalawa. Data collection techniques using observation, questionnaires, and tests. Data analysis techniques using normality tests, linearity tests, and partial correlation. The results of this study indicate: 1) the internalization of the TGT learning model based on traditional games among students is in the Good category with a percentage of 38.71% or 12 out of 31 students; 2) there is a significant relationship between the TGT learning model based on traditional games and students' numeracy skills with a significance value Sig. (2-tailed) of 0.000 < 0.05, and calculated r (Pearson Correlations) of 0.784 > r table of 0.355; 3) there is a significant correlation between the TGT learning model based on traditional games and students' social skills with a significance value Sig. (2-tailed) of 0.000 < 0.05, and calculated r (Pearson Correlations) of 0.844 > r table of 0.355.